What is the effect of obesity on piperacillin and meropenem trough concentrations in critically ill patients? - Alobaid, Abdulaziz S.; Brinkmann, Alexander; Frey, Otto R.; Roehr, Anka C.; Luque, Sonia; Grau, Santiago; Wong , Gloria; Abdul Aziz, Mohd. Hafiz; Roberts, Michael S.; Lipman, Jeffrey; Roberts, Jason A. (Oxford Journals, 2015)
The objectives of this study were to determine the effects of obesity on unbound trough concentrations and on the achievement of pharmacokinetic (PK)/pharmacodynamic (PD) targets of piperacillin and meropenem in critically ill patients. This study retrospectively analysed therapeutic-drug-monitoring data from ICU databases in Australia, Germany and Spain, as well as from a large PK study. The presence of obesity was defined as a BMI ≥30 kg/m2, and patients were also categorized based on level of renal function. The presence of obesity was compared with unbound piperacillin and meropenem trough concentrations. We also used logistic regression to describe factors associated with the achievement of the PK/PD targets, an unbound concentration maintained above the MIC breakpoint (100% fT>MIC and 100% fT>4×MIC) of Pseudomonas aeruginosa. In all, 1400 patients were eligible for inclusion in the study. The median age and weight were 67 years (IQR 52-76 years) and 79 kg (69-90 kg), respectively, and 65% of participants were male. Significantly lower median piperacillin trough concentrations [29.4 mg/L (IQR 17.0-58.0 mg/L)] were found in obese patients compared with non-obese patients [42.0 mg/L (21.5-73.5 mg/L)] (P = 0.001). There was no difference for meropenem trough concentrations [obese 10.3 mg/L (IQR 4.8-16.0 mg/L) versus non-obese 11.0 mg/L (4.3-18.5 mg/L); P = 0.296]. Using logistic regression, we found that the presence of obesity was not associated with achievement of 100% fT>MIC, but the use of prolonged infusion, a creatinine clearance ≤100 mL/min, increasing age and female gender were for various PK/PD targets for both piperacillin and meropenem (P < 0.05). This large dataset has shown that the presence of obesity in critically ill patients may affect piperacillin, but not meropenem, unbound trough concentrations.